Information Literacy Training on the Preparedness of Garut People in Facing Landslide Threats - Eldi Mulyana Mulyana; Ade Suherman; Triani Widyanti; Tetep Tetep; Asep Supriyatna; Fadlika Sulaeman; Hilmi Hilmi; Nurdin Miptahul Ulum; Irwan Nurkholis; Nia Kurniawan (Fakultas Kewirausahaan Universitas Garut, 2020)
The purpose of this study was to analyze the impact of information literacy on the preparedness of the people of Garut Regency in facing the threat of landslide. The data ini this study are the people of Garut Regency who have been affected by landslides based on the 2010 population census based on gender. The research method uses quantitative patterns in the form of surveys. The results showed that the magnitude of the impact of the ability to identify and find the location of information on public awareness in facing the threat of landslides by 38%. The impact of landslide information literacy can increase the preparedness of the people of Garut Regency by 57%. The conclusion is the impact of information literacy has a significant impact on the preparedness of the people of Garut Regency in facing the threat of landslides.